The effect of corporate social responsibility on job pursuit intentions: Contributes from person-organization fit and organizational attractiveness - Silva, V. H.; Duarte, A. P.; Simões, E.; Neves, J. G. (Working papers series on social responsibility, ethics and sustainable business, 2019)
Previous studies suggest that the corporate social performance of organizations influences their attractiveness as a future workplace (e.g., Gomes & Neves, 2010; Greening & Turban, 2000). People tend to considerer an organization as more attractive when, knowing its socially responsible practices, they perceive higher levels of person-organization fit (Kim & Park, 2011). The present study analyzes how the relation between these variables translates into job pursuit intentions, namely intention to apply for a job vacancy (IAJV). In the research, CSR perception was manipulated in order to observe its effect on IAJV through the mediating effect of perceived person-organization fit and organizational attractiveness. Participants (n = 260) were randomly subjected to two experimental conditions by responding to an electronic questionnaire containing the description of an organization that implements (i.e., the high involvement condition) or not (i.e., the low involvement condition) a set of CSR practices. This was followed by questions about other variables of interest. The results of multiple mediation analyses using PROCESS (Hayes, 2013) support the proposal that CSR indirectly affects participants’ IAJV, through perceived person-organization fit and organizational attractiveness.